Unfired Bricks Mixed with Para Rubber Latex for Sustainable Construction Materials - Janpetch, Natapong; Trakolkul, Chokchai; Plitsiri, Itthi; Thepjunthra, Wiphada (Civil Engineering Journal, 2024)
This paper aims to study the development of bricks without burning, mixing para rubber latex, and compressing them with the technology of interlocking block production. The ratio of cement, lateritic soil, and water used in the mix was 1:6:11, while the percentage of para rubber latex (PRL) added was 2.5, 5, 7.5, 10, and 12.5% of the cement weight. The optimal PRL content (2.5%–7.5% by cement weight) enhances compressive strength, reduces water absorption, and improves durability, meeting the Thai industrial standard (TIS 77-2545). The PRL7.5 mixture achieved the highest performance, with a compressive strength of 21.42 MPa and a water absorption rate of 7.55%. These advancements are credited to the polymer film network formed from PRL during the hydration process, which strengthens particle bonds and reduces porosity. However, PRL content exceeding 7.5% leads to performance reductions, attributed to thicker polymer films and particle aggregation, which create larger voids within the material. Furthermore, the modified unfired bricks demonstrated enhanced crack resistance, increased ductility, and superior thermal insulation properties. Thermal tests of masonry walls confirmed that unfired bricks provide better thermal insulation. Temperature measurements revealed that houses constructed with unfired bricks consistently maintained cooler indoor temperatures compared to those made with fired bricks, indicating improved thermal efficiency. Environmentally, unfired bricks eliminate carbon emissions from firing processes and offer simpler, more energy-efficient production methods. These bricks provide sustainable alternatives to fired bricks, promoting both environmental and economic benefits for brick-making communities. Doi: 10.28991/CEJ-2024-010-12-05 Full Text: PDF